2014
DOI: 10.1111/jorc.12055
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Care for Renal Transplant Recipients: An Evaluation of Service Delivery and Outcomes

Abstract: Nutrition care provided did not meet guideline recommendations, highlighting difficulty in implementing evidence to practice. Significant weight gain was evident particularly in patients classified as 'healthy weight' at the time of transplant. Long-term, prospective studies are needed to determine the effectiveness of implementing nutrition care to attenuate weight gain and improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The correlation between weight at baseline and 6 months was estimated as 0.9, based on data showing a mean difference in weight of 3.2 kg (SD 5.9 kg) between 1 and 6 months of 1299 kidney transplant recipients who received their kidney transplant in Auckland between 1991 and 2012 (unpublished observations, data on file), where the correlation was 0.9514. Similar findings were found in an analysis of weight change post-transplant in a comparable population of 156 transplant recipients in Brisbane, Australia (mean weight change 3.3 kg, SD 6.0 kg) (Campbell KL, personal communication) [18]. …”
Section: Methodssupporting
confidence: 76%
See 2 more Smart Citations
“…The correlation between weight at baseline and 6 months was estimated as 0.9, based on data showing a mean difference in weight of 3.2 kg (SD 5.9 kg) between 1 and 6 months of 1299 kidney transplant recipients who received their kidney transplant in Auckland between 1991 and 2012 (unpublished observations, data on file), where the correlation was 0.9514. Similar findings were found in an analysis of weight change post-transplant in a comparable population of 156 transplant recipients in Brisbane, Australia (mean weight change 3.3 kg, SD 6.0 kg) (Campbell KL, personal communication) [18]. …”
Section: Methodssupporting
confidence: 76%
“…The extent of weight gain after transplant has been shown be significantly affected by baseline BMI [18]; gender will be included as a covariate due to its use as a stratification variable in the randomisation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A retrospective study showed that 32% of patients who had normal body mass index and 23% of overweight patients were classified as obese 12 months after renal transplant. 17 Potential factors causing weight gain after renal transplant include use of immunosuppressive agents to protect the implanted organ, lack of physical activity, and other life style changes such as dietary intake. 16 Moreover, age , sex, 2,14,16,18 race, 2,16,18 absence of acute rejection, 2 and genetic 14,16 and psychological effects related to stress 16 can play roles in weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…Weight gain after kidney transplantation is very often observed and it has been reported to be between 10% and 35%, mainly during the first year after transplant [ 1 4 ]. Post-transplant overweight and obesity may lead to negative post-transplant outcomes, such as graft loss and cardiovascular events [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%